Reflux synthesis and physicochemical characterisation of MoVTeNbOx catalyst for propane oxidation into acrylic acid - Ismail, Ahmad Zaidi (2011)
The abundance of propane and its low price is one of the main factors that made selective oxidation of this light alkane to acrylic acid through heterogeneous catalytic pathway receives intensive research. MoVTeNbOx a quarternary metal oxide catalyst is reported to have shown the best performance for the direct oxidation of propane to acrylic acid to this date. In this work, MoVTeNbOx catalysts were prepared by reflux method. Synthesis parameters such as reflux time and drying method were found to have profound effect on the catalyst structure and chemical properties. Spray drying was found to give precursor which upon calcinations produced better formation of M1 and M2 phase MoVTeNbOx catalyst compared to samples dried by rotary evaporation method. This is proved by the X-ray diffragtogram of the samples as it shown peak at 2=6.6, 7.9, 9.0, 22.1 and 45 which correspond to orthorhombic (M1) phase and 2=28.3, 36.2 and 50 of hexagonal (M2) phase. Longer reflux time gave better structura formation and higher specific surface area (SBET) thus led to a better catalyst performance of samples dried using spray dry method. Investigation on calcinations environment revealed that calcination in air followed by calcination in nitrogen flow gives better catalyst (catalyst B2). Catalyst B2 gave higher specific surface area (SBET)and oxygen removed in H2-TPR which is 5.3 m2g-1 and 2.8x1021 atomg-1 respectively. Thus indicates that sample B2 is an active catalyst. However calcination in air should not exceed 1 hour as longer calcination in air will impede the properties of the catalyst. Finally, washing the synthesized catalyst with hydrogen peroxide managed to eliminate the non-active M2 phase and improved the formation of the M1 phase. This is proved by a more significant X-ray diffraction patterns at 2 = 6.6, 7.9, 9.0, 22.1, 27.0 and 45° with absences of diffraction peaks at 2 = 28.3, 36.2 and 50 that related to the existence of M2 phase for after washing with H2O2 sample (B2W). Higher SBET also observed for sample B2W which is 12.5 m2g-1 compared to 5.3 m2g-1 for sample before washing (B2). The catalytic tests were done at three different reaction temperatures which are 653, 673 and 693 K. Propane conversion was found to increase when the temperature was increased up to 693 K. Catalyst obtained from a longer reflux time (72 hours) and dried using a spray dry method give a better activity which is 6.53% at 693 K compared to the catalyst obtained from a shorter reflux time (24 hours) with 4.55% or the sample dried using rotary evaporator (3.76%) at the same temperature. The catalytic test of the catalyst after washing with H2O2 (B2W) showed very promising propane conversion (22.01 %) and higher reaction selectivity towards acrylic acid (24.21%).